Рід Rosa L. у гербарії НБС ім. М.М. Гришка НАН України - Rubtsova, O.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2004)
The results of examination of specimens of the genus Rosa L. of M.M. Grishko National Botanical Gardens herbarium collection are presented. History of collection, its structure and modern state are examined.